Crescimento e acúmulo de nutrientes do capim-marandu e resposta às adubações nitrogenada e fosfatada - Bezerra, Márcio Gleybson da Silva (2019)
Pastures have high socioeconomic importance, since they constitute the base of support of Brazilian livestock, representing the main food source of ruminants. Among the forage grasses cultivated stands the Marandu grass, occupying about 60 million hectares. When properly managed, it has high productivity and high response to fertilization. Given the above, the objective of this work was to evaluate the accumulation of dry matter and nutrients by marandu grass and response to nitrogen and phosphate fertilizers. The experiments were conducted in a Quartzarenic Neossol in Macaíba-RN. Dry matter and nutrient accumulation was evaluated from January to August 2017, corresponding to the first two crop production cycles. In the first production cycle, the plants were collected at 30, 40, 50, 60, 70, 80 and 90 days after sowing. In the second cycle, plant samples were collected at 30, 40, 50, 60, 70 and 80 days after the first cut. In both production cycles, the height and accumulation of dry matter and macronutrients in the shoot were evaluated. The response of Marandu grassland to N and P doses was evaluated from January 2017 to January 2018. The experimental design was a randomized block design with 11 treatments and four replications. The treatments consisted of 5 nitrogen doses (0, 400, 800, 1200 and 1600 kg ha-1 year-1 of N) and 5 doses of phosphorus (0, 50, 100, 150 and 200 kg ha-1 year-1). P2O5), plus a control treatment without the application of N or P2O5. The variables evaluated in six sections were plant height, leaf / stem ratio, N and P content in the diagnostic sheet, crude protein content, dry matter production and accumulated N and P in the plant. In the first and second production cycle, dry matter accumulation increased throughout the plant cycle, especially from the second half of the cycle. In general, macronutrient accumulation followed dry matter accumulation. In both production cycles of marandu grass, at the time of harvesting, the decreasing order of macronutrient accumulation in the shoots was K> N> Mg> Ca> P> S. Plant growth and yield Marandu forage increased as a function of increasing N and P2O5 rates. Forage quality increased with increasing N rates, but was not influenced by phosphate fertilization. The estimated annual N dose for marandu grass yield, equivalent to 90% of the maximum yield obtained, was 860 kg ha-1 year-1, while for P this value was estimated at 100 kg ha-1 year-1 of P2O5.